Enhancing Research Visibility: Analyzing Anesthesia Faculty at AIIMS, New Delhi, on Google Scholar (TULSSAA Journal, 2025)
Research visibility is crucial in enhancing a researcher's academic recognition, accessibility, and impact. This study examines the research productivity and scholarly influence of faculty members in the Anesthesia Department at AIIMS, New Delhi, using Google Scholar metrics, including total publications, citation count, h-index, and i10-index. Among the 48 faculty members, only 27 have a Google Scholar profile, and just 12 have integrated a verified email ID, indicating limited adoption of the platform for academic visibility. The analysis of scholarly output reveals that Associate Professor Dr Anju Gupta has the highest number of publications (532). At the same time, Additional Professor Dr Souvik Maitra leads in citations (5,969), h-index (33), and i10-index (66), reflecting a strong research influence. Mid-career faculty members, particularly additional and associate professors, demonstrate higher engagement in research, while senior professors appear to focus more on mentorship and administrative responsibilities. The study also highlights gender representation in research, with female faculty members making substantial contributions. The findings emphasize the need for increased institutional support and awareness regarding the benefits of Google Scholar to enhance research visibility, foster collaboration, and strengthen the department's academic impact.